Measuring Sustainability Practices of Indian Banks: A Way Forward (International Journal of Environmental Sciences, 2025)
Banks are attempting to incorporate sustainable practices into their operations, which is an important component of growth. The present study seeks to measure and compare sustainability practices (environmental, social, governance, and sector-specific) across banks. For this purpose, the top five banks on the basis of market capitalization as of October 4, 2023, comprise the sample set. Content analysis has been applied as a data collection tool. The Kurskal-Wallis test was applied to compare sustainability practices across banks. The analysis reveals that banks differ significantly in environmental, sector-specific, and governance practices. Further, Axis Bank outperforms the other four banks in terms of environmental practices, ICICI in sector-specific practices, and HDFC in governance practices. Finally, efforts have been made to come up with discussion and recommendations in comparison to J.P. Morgan Chase, the leading bank in the United States.